2018
DOI: 10.3892/etm.2018.6195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forkhead box protein M1 on trophoblast invasion and its role in preeclampsia development

Abstract: The present study aimed to investigate the expression of the forkhead box protein M1 (FOXM1) in the placenta of patients with preeclampsia, and its effect on trophoblasts. A total of 28 patients with preeclampsia and 30 patients without preeclampsia (controls) who underwent cesarean section and were admitted to the Affiliated Hospital of Qingdao University between June 2013 and September 2016 were enrolled in the present study. The expression of FOXM1 in placental tissues was examined by reverse transcription-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…FOXM1 is a transcription factor necessary for tumor proliferation, and its expression level is often related to the degree of malignant progression of tumors. It was reported that FOXM1 expression was downregulated in the placental tissues of patients with preeclampsia, and FOXM1 silencing significantly decreased cell proliferation and migration [ 30 , 31 ]. FOXM1 mRNA and protein expression was downregulated after transfection of FOXM1 but was rescued by cotransfection with the miR-1244 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 is a transcription factor necessary for tumor proliferation, and its expression level is often related to the degree of malignant progression of tumors. It was reported that FOXM1 expression was downregulated in the placental tissues of patients with preeclampsia, and FOXM1 silencing significantly decreased cell proliferation and migration [ 30 , 31 ]. FOXM1 mRNA and protein expression was downregulated after transfection of FOXM1 but was rescued by cotransfection with the miR-1244 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The downstream target genes of miR‐134‐5p were predicted on the Starbase, RNA22, and miRTarBase databases, and the intersections were identified (Figure 4a), from which we focused on FOXM1 that has been reported the downregulation in PE (Cui et al, 2018; Mao et al, 2021). Therefore, we selected FOXM1 as the downstream target gene of miR‐134‐5p.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggested that the miR‐134‐5p/FOXM1 axis is the downstream mechanism of HDAC4 in PE. Moreover, as a transcription factor, silencing of FOXM1 has been shown to decrease the expression of vascular endothelial growth factor (VEGF) in PE development (Cui et al, 2018). However, whether VEGF can act as the downstream target of the HDAC4/miR‐134‐5p/FOXM1 axis in PE requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-eclampsia (PE) is a pregnancy complication that occurs after 20 weeks of gestation and is characterized by hypertension, proteinuria, and multiple organ dysfunction ( 1 ). It has been reported that approximately 2–8% of first pregnancies are diagnosed with PE, and is the most important cause of perinatal maternal and infant mortality ( 2 ). Meanwhile, PE is a major risk factor for poor maternal and child health and substantially increases the risk of miscarriage, acute renal failure, and low birth weight stillbirth ( 3 ).…”
Section: Introductionmentioning
confidence: 99%